Pengaruh Tingkat Pengangguran, Tingkat Kemiskinan dan Upah Minimum Provinsi (UMP) terhadap Tindak Kriminalitas di Indonesia Tahun 2021-2023 - Adamvin Satria Dharmawan; Nurul Istiqomah; Putri Nurmawati; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Based on data from the Central Statistics Agency (BPS) from 2021 to 2023, the crime rate in Indonesia increased by 345,510 cases. This increase indicates social problems, particularly in the economic sector. Factors such as high unemployment, high poverty rates, and low minimum wages are the main causes driving crime. When people's basic needs are not met, the potential for deviant behavior to meet their living needs tends to increase. This study aims to analyze the influence of unemployment, poverty, and the Provincial Minimum Wage (UMP) on crime rates in Indonesia, both partially and simultaneously. The study uses a quantitative approach with secondary data sources obtained from official BPS publications. The data used is panel data, namely a combination of time series (time span) and cross-section (across regions/provinces) data for the period 2021–2023. Data analysis was performed using a panel data regression model with a Fixed Effect Model (FEM) approach after undergoing the Hausman Test. The results show that partially, the three variables—unemployment, poverty, and the UMP—have a significant influence on crime rates. Simultaneous testing also showed that collectively, these three variables significantly influence the crime rate. Furthermore, the coefficient of determination (R²) test result of 93.5% indicates that unemployment, poverty, and the minimum wage (UMP) variables are able to explain most of the variation in crime rates in Indonesia during the study period, while the remaining 6.5% is influenced by other variables not included in the model. This finding emphasizes the importance of improving the economic conditions of the community through job creation, poverty alleviation, and minimum wage adjustments as preventative measures to reduce crime rates in Indonesia.